Personnel attitudes toward people with mental illness at a psychiatric hospital in Taiwan. (June 2016) - Chen, Ming-De; Chang, Yen-Ching
Background: The attitudes of psychiatric hospital personnel are critically related to the quality of mental health care, but few studies have investigated this issue. Aims: This study is aimed at an exploration of the attitudes of psychiatric hospital personnel toward people with mental illness and at an examination of the associated factors. Method: A self-report questionnaire, the Mental Illness Attitude Scale (MIAS), was used to collect data from psychiatric hospital personnel in Taiwan ( n = 290). The MIAS included 46 items and 4 dimensions: acceptance, rehabilitation and prognosis, social distance and recommendations for interventions. Results: Rehabilitation and prognosis had the highest item average scores (4.03) and social distance had the lowest item average scores (3.22). Stigmatization and the number of different types of contacted clients were two significantly associated attitude factors. Conclusion: Psychiatric hospital personnel in Taiwan tend to have positive attitudes toward people with mental illness in general situations but hold less positive attitudes in terms of community integration-related issues and intimate relationships. More evidence-based community services should be conducted to decrease personnel concerns about the successful community integration of those who are mentally ill. Future studies can investigate the concept and impact of stigmatization more deeply.